Application of veno-venous extracorporeal membrane oxygenation in lymphoma patients with severe acute respiratory distress syndrome : a case series = Primjena veno-venske izvantjelesne membranske oksigenacije kod pacijenata s limfomom i teškim akutnim respiratornim distresnim sindromom : serija slučajeva - Tokmadžić, Dorian (Array, 2021)
Aim: To report the clinical courses of two patients, one with Hodgkin"s lymphoma (HL) and one with Non-Hodgkin"s lymphoma (NHL), who developed severe refractory acute respiratory distress syndrome (ARDS) and were treated with veno-venous extracorporeal membrane oxygenation (VV ECMO). Case report: Both patients developed chemotherapy-associated febrile neutropenia followed by pneumonia and ARDS, after which they were transferred to the intensive care unit. Their respiratory failure deteriorated despite endotracheal intubation with protective mechanical ventilation, at which point a decision for VV ECMO initiation was made. Both patients had complicated treatment courses and developed severe ECMO-associated complications. The most important complications of ECMO support in our HL patient were cardiac arrest; right atrial laceration with pericardial tamponade which needed surgical treatment; right leg ischemia which required transfemoral amputation; thrombosis within the membrane oxygenator; several septic episodes with severe hemodynamic instability; and right sided tension pneumothorax. Despite all difficulties, the patient was successfully weaned from ECMO. Unfortunately, he died prior to hospital discharge as a result of sepsis with multiple organ failure. The most significant ECMO-induced complications in our NHL patient were severe bleeding incidents, most notably diffuse oropharyngeal and continuous bilateral pulmonary hemorrhage; superimposed bacterial pneumonia; extensive pneumomediastinum and subcutaneous emphysema. Despite all therapeutic efforts, the patient died during ECMO treatment because of respiratory decompensation. Conclusions: The patients with hematologic malignancies (HMs) undergoing ECMO support have poor outcomes, with high rates of severe ECMO-induced complications. Further studies focusing on patient selection and issues concerning prevention, diagnosis and treatment of ECMO-associated complications are needed.